Runt-related transcription factors: from pathogenesis to therapeutic targets in multiple-organ fibrosis - Feng, Yuan; Mao, Tianshi; Yi, Jifei; Zhang, Na; Gu, Yinying; Shen, Huifen; Chen, Jie (Frontiers in Cell and Developmental Biology, 2025)
Fibrosis is a partially manageable process that leads to scarring and tissue hardening by prompting myofibroblasts to deposit significant amounts of extracellular matrix (ECM) following injury. It results in detrimental consequences and pathological characteristics, which hinder the functioning of associated organs and increase mortality rates. Runt-related transcription factors (RUNX) are part of a highly conserved family of heterodimer transcription factors, comprising RUNX1, RUNX2, and RUNX3. They are involved in several biological processes and undergo various forms of post-translational modification. RUNX regulates multiple targets and pathways to impact fibrosis, indicating promise for clinical application. Therefore, its significance in the fibrosis process should not be disregarded. The review begins with an objective description of the structure, transcriptional mechanism, and biological function of RUNX1, RUNX2, and RUNX3. A subsequent analysis is made of their physiological relationship with heart, lung, kidney, and liver, followed by a focus on the signaling mechanism of RUNX in regulating fibrosis of these organs. Furthermore, potential agents or drugs targeting RUNX for treating organ fibrosis are summarized, along with an evaluation of the therapeutic prospects and potential value of RUNX in fibrosis. Further research into RUNX could contribute to the development of novel therapeutic approaches for fibrosis.